2022
DOI: 10.21037/atm-22-2126
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S promotes ion channel reconstruction to regulate colonic motility in rats with dinitrobenzene sulfonic acid-induced colitis

Abstract: Background: Hydrogen sulfide (H2S) is a newly recognized endogenously generated gasotransmitter.Endogenous H2S has been shown to be related to several gastrointestinal diseases, including irritable bowel syndrome, Crohn's disease, and ulcerative colitis. We explored the functional role of H2S in colitis and investigated the underlying mechanism.Methods: Rats were randomly divided into control, model, and sodium hydrosulfide (NaHS) groups. Rat colitis was evaluated using the disease activity index and hematoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Hydrogen sulfide, similarly to secondary bile acids and TMAO, can multidirectional affect inflammation, oxidative stress, and carcinogenesis[ 155 , 191 ]. Various authors have demonstrated both its inflammatory[ 192 ] and anti-inflammatory effects[ 193 , 194 ], as well as its carcinogenic[ 195 , 196 ] and anticancer properties[ 197 , 198 ]. For example, some researchers have demonstrated that hydrogen sulfide may be associated with the breakdown of disulfide bonds in the mucus double layer in the colon wall, leading to inflammation and translocation of bacteria and toxins[ 199 ].…”
Section: Products Of Bacterial Metabolism and Their Role In Health An...mentioning
confidence: 99%
“…Hydrogen sulfide, similarly to secondary bile acids and TMAO, can multidirectional affect inflammation, oxidative stress, and carcinogenesis[ 155 , 191 ]. Various authors have demonstrated both its inflammatory[ 192 ] and anti-inflammatory effects[ 193 , 194 ], as well as its carcinogenic[ 195 , 196 ] and anticancer properties[ 197 , 198 ]. For example, some researchers have demonstrated that hydrogen sulfide may be associated with the breakdown of disulfide bonds in the mucus double layer in the colon wall, leading to inflammation and translocation of bacteria and toxins[ 199 ].…”
Section: Products Of Bacterial Metabolism and Their Role In Health An...mentioning
confidence: 99%